2018
DOI: 10.15294/biosaintifika.v10i1.13398
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Clorella vulgaris on Wistar Rat Kidney Induced by CCl4: A Histopathological Review

Abstract: Kidney is very susceptible to damage by toxicological compounds such as carbon tetrachloride (CCL). CCL produce free radicals, which cause lipid peroxidation and kidney damage and free radical release, which can be prevented by the administration of exogenous antioxidants, such as Chlorella vulgaris. The aim of study was to determine an effect of antioxidant of C. vulgaris on the histopathological features of Wistar rat kidney which is induced by CCL. Experimental study with completely randomized design. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Whilst, phenolic and carotenoid compounds within microalgae Chlorella vulgaris can be utilized as exogenous antioxidants. In line with the study of Susatyo et al (2018), in this research, the antioxidants contained in red okra extract can stabilize free radicals. this is indicated by increasing levels of SOD while MDA levels drop.…”
Section: Effect Of Roe On Sod and Mda Levels In Serumsupporting
confidence: 73%
See 1 more Smart Citation
“…Whilst, phenolic and carotenoid compounds within microalgae Chlorella vulgaris can be utilized as exogenous antioxidants. In line with the study of Susatyo et al (2018), in this research, the antioxidants contained in red okra extract can stabilize free radicals. this is indicated by increasing levels of SOD while MDA levels drop.…”
Section: Effect Of Roe On Sod and Mda Levels In Serumsupporting
confidence: 73%
“…Vitamin C, carotenoids, phenolic, and flavonoid compounds are used as antioxidants that can capture and scavenge free radicals, inhibit the synthesis of the radicals by chelating metal ions and neutralize them from causing molecular oxidation in the cells (Kumar & Pandey, 2013;Petropoulos et al, 2017). Research by Susatyo et al (2018) reports that endogenous antioxidants as protective agents in the body can reduce because free radicals increase.…”
Section: Effect Of Roe On Sod and Mda Levels In Serummentioning
confidence: 99%
“…This can be due to C. vulgaris and A. maxima which function as antioxidants. C. vulgaris as an antioxidant can be used to prevent kidney damage, as in previous studies conducted by Susatyo et al (2018) that C. vulgaris extract can reduce kidney damage exposed to CCl4. The ability of C. vulgaris extract provides protection against oxidative stress and free radicals associated with antioxidant compounds in it.…”
Section: Glomerular Kidney Histologymentioning
confidence: 94%
“…
Previous studies have indicated that algae such as Chlorella vulgaris, Ulva lactuca, and Porphyra yezoensis exhibit potential nephroprotective effects in the context of diabetic kidney disease. 5,6,7 These algae contain common metabolites such as phycocyanin, chlorophyll, carotenoids, vitamins, minerals, polysaccharides, and essential fatty acids. These metabolites, known for their antioxidant properties, have been suggested to play a role in attenuating oxidative stress and inflammation in the kidneys, thereby potentially contributing to the management of diabetic kidney disease.
…”
mentioning
confidence: 99%